LEGALITY OF MARIJUANA USE IN THE NEED FOR MEDICAL TREATMENT IN INDONESIA (JUDGING FROM LAW NUMBER 36 OF 2009 CONCERNING HEALTH AND LAW NUMBER 35 OF 2009 CONCERNING NARCOTICS) - Marisca Evalina Gondokesumo; Nabbilah Amir (Journal Equity of Law and Governance, 2021)
Marijuana according to positive law in Indonesia including narcotics group I which is considered the most dangerous because it has a very high addiction and the plant has long been viewed negatively by the wider community, but behind the negative stigma of the community it turns out that marijuana contains many benefits for health care needs. The issue for legalizing cannabis for medical purposes was initiated by the Nusantara Marijuana Circle organization. This research aims to examine whether the use of marijuana for medical purposes in Indonesia has received legalization. The research method used is empirical juridical. The legal materials use are primary legal materials and secondary legal materials. The results showed that because the law was born and developed continuously to build and change itself towards a better level of perfection. With so much potential contained in cannabis, especially its presence in the health sector it is appropriate for state officials to revise policies on narcotics. Legalization of cannabis can be used as an alternative solution for the Indonesian state to improve the welfare of the community because it can be used as an alternative to the country's industrial commodities, especially in the field of health services.